Felony juggler - Jillette, Penn (Akashic Books, 2025)
"In the early 1970s, Poe is living a nomadic life, hopping trains, sleeping rough, and juggling to feed himself. He eventually settles in Philadelphia and masters his street act before ever-growing crowds. When one of his fellow buskers presents him with an opportunity--a bank heist--he should have refused, an innocent bystander is killed, and he splits town a felon. Unable to resist the lure of performing, he resurfaces halfway across the country as a regular act in a Renaissance Fair(e). Unfortunately, his notoriety outs him to the criminal organization who believes he took something of importance from them during the bank heist. Using all of the wit and misdirection that has made him the best street performer anyone has ever seen, Poe must outsmart and outmaneuver them in order to return to the peaceful life of juggling."--